2021
DOI: 10.1002/ejsp.2740
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to reconciliation and forgiveness among victim groups of unacknowledged past trauma and genocide

Abstract: Groups in conflict often resist efforts toward reconciliation with the outgroups. Despite the growing research examining processes underlying support for reconciliation, we know little about how resentment might drive members of victim groups that have experienced violence and atrocities to oppose reconciliation and reduce their willingness to forgive the perpetrator group. Using the context of the Turkish–Armenian conflict, the present research investigated the association of ingroup identification, ingroup g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…For ethnic minority groups whose rights are continuously denied or not acknowledged by majority group members in conflict contexts, these negative views or attitudes toward outgroups may be justifiable because these views may protect minority group members from superficial reconciliation (for a discussion on victim groups, see Nadler, 2012). Therefore, ingroup identification for minority group members may be seen as a double-edged sword: leading to more positive outcomes for the ingroup, whereas having the potential to lead to more negative consequences for intergroup relations (see, e.g., Uluğ et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…For ethnic minority groups whose rights are continuously denied or not acknowledged by majority group members in conflict contexts, these negative views or attitudes toward outgroups may be justifiable because these views may protect minority group members from superficial reconciliation (for a discussion on victim groups, see Nadler, 2012). Therefore, ingroup identification for minority group members may be seen as a double-edged sword: leading to more positive outcomes for the ingroup, whereas having the potential to lead to more negative consequences for intergroup relations (see, e.g., Uluğ et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…The current research also enhances the understanding of the role of attachment in conflict. Prior research has either only measured glorification but not attachment (Bilali, 2013; Uluğ et al., 2021), or produced rather mixed findings regarding the conflict implications of attachment (e.g., Leidner, 2015; Leidner et al., 2010; Li et al., 2016; Rovenpor et al., 2016). One potential conclusion drawn from the mixed findings is that whereas glorification is a robust and consistent predictor of negative intergroup outcomes, the role of attachment in intergroup relations is more variable, depending on the intergroup context and outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the link between glorification and retributive justice, Selvanathan and Leidner (2020) showed that attachment promoted restorative justice, which in turn predicted support for normative collective action. Other studies, however, have not consistently found a link between attachment and various intergroup outcomes (Leidner, 2015; Leidner & Castano, 2012; Li et al., 2016, 2018; Rovenpor et al., 2016), or only measured glorification but not attachment (Bilali, 2013; Uluğ et al., 2021).…”
Section: Glorification Attachment and Conflict Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconciliation has typically been measured in terms of people's willingness to reconcile (e.g., Biro et al., 2004) or to engage in actions that promote reconciliation (e.g., Pham et al., 2004; Tropp et al., 2017), yet people's willingness to reconcile is likely to be shaped profoundly by their beliefs about reconciliation and what the reconciliation process might take given the many emotional and relational obstacles involved (Čehajić‐Clancy & Bilewicz, 2017). Only rarely have researchers assessed people's actual beliefs about reconciliation, such as whether it is deemed to be necessary (see Halloran, 2007; Uluğ et al., 2021), or whether it is perceived to be possible (Cehajic‐Clancy & Bilewicz, 2017). Relatedly, the topic of reconciliation involves questions about whether people see greater integration of conflicting groups as a desired and valued goal worthy of being pursued (Cohen‐Chen et al., 2017; Halperin & Schwartz, 2010; Leach & Williams, 1999) and the extent to which they are personally willing to engage in social relations with groups on the other side of the conflict (Čehajić‐Clancy et al., 2023).…”
Section: Introductionmentioning
confidence: 99%